Diffraction driven steep rise of spin structure function gLT= g1+ g2 at small x and DIS sum rules - Ivanov, I.P.; Nikolaev, N.N.; Pronyaev, A.V.; Schäfer, W. (Physics letters. B, 1999)
We derive a unitarity relationship between the spin structure function g LT( x, Q 2)= g 1( x, Q 2)+ g 2( x, Q 2), the LT interference diffractive structure function and the spin-flip coupling of the pomeron to nucleons. Our diffractive mechanism gives rise to a dramatic small- x rise g LT (x,Q 2)∼g 2(x, Q 2)∼(1/x) 2(1+δ g) , where δ g is an exponent of small- x rise of the unpolarized gluon density in the proton g(x, Q 2) at a moderate hard scale Q 2 for light flavour contribution and large hard scale Q 2∼m f 2 for heavy flavour contribution. It invalidates the Burkhardt-Cottingham sum rule. The found small- x rise of diffraction driven g LT( x, Q 2) is steeper than given by the Wandzura-Wilczek relation under conventional assumptions on small- x behaviour of g 1( x, Q 2).